2007
DOI: 10.5688/aj710234
|View full text |Cite
|
Sign up to set email alerts
|

Use of Reflective Portfolios in Health Sciences Education

Abstract: Reflective portfolios are a collection of evidence that through critical reflection on its contents demonstrate achievement as well as personal and professional development. The purpose of this paper is to provide a review of the literature on the use of reflective portfolios and to develop a set of factors to guide schools and colleges of pharmacy as they implement reflective portfolios into their respective curricula as stated in Standards 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 32 publications
0
60
0
Order By: Relevance
“…4,9 Additionally, the American Society of Health System Pharmacists stated that "Pharmacists in organized health-care settings have a professional obligation to participate actively in and increase pharmacy-related and drug-related research efforts." 9 However, the opportunities for students to learn about basic research are limited. In a survey reported by Murphy, et al, 6 41.0% of surveyed Pharm.D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9 Additionally, the American Society of Health System Pharmacists stated that "Pharmacists in organized health-care settings have a professional obligation to participate actively in and increase pharmacy-related and drug-related research efforts." 9 However, the opportunities for students to learn about basic research are limited. In a survey reported by Murphy, et al, 6 41.0% of surveyed Pharm.D.…”
Section: Discussionmentioning
confidence: 99%
“…Key topics were defined according to reported findings and elective research rotation supportive rationale as previously reported. [4][5][6][7][8][9][10] Thirty-five topics were chosen and each topic was sequentially numbered in order to provide differentiation. The investigators were able to obtain 15 reflections from six of the 12 student pharmacists from the Experiential Education office of the college.…”
Section: Data Collection and Evaluationmentioning
confidence: 99%
“…It allows the collation and integration of evidence on competence and performance from different sources to gain a comprehensive picture of everyday practice. Student faculty link is an important component in the portfolio process and can serve as a platform for discussion between students and faculty members to help theory-practice gap [19]. It is just not a logbook with learning experiences but evidence of annotated documentation of the learner's reflections regarding his or her learning.…”
Section: A Proposed Solutionmentioning
confidence: 99%
“…10 Reflection exercises have been readily implemented into doctor of pharmacy (PharmD) curricula, but challenges and questions still need to be answered regarding the effectiveness of such activities in developing reflective practitioners. [11][12][13][14] One commonly cited difficulty with these exercises is the challenge of assessing the quality and/or level of the reflection. 14 Commonly, the literature describes reflection activities compiled in a portfolio and some level of assessment and feedback given to students, typically in the form of a structured rubric that rates the general quality of the work.…”
Section: Introductionmentioning
confidence: 99%